1995
DOI: 10.1016/s0014-4835(95)80060-3
|View full text |Cite
|
Sign up to set email alerts
|

Light-evoked oxygen responses in the isolated toad retina

Abstract: Transient changes in retinal oxygen in response to light stimuli were studied to further understand the light-evoked change in oxygen consumption. Double-barreled microelectrodes, which measured oxygen and local voltage simultaneously, were positioned near the photoreceptor inner segments of the toad neural retina-retinal pigment epithelium--choroid preparation. Light-evoked oxygen responses were measured in a normal [Na ÷] solution, and in a test solution with lowered extracellular [Na ÷] to inhibit Na*/K * p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 17 publications
(16 reference statements)
3
23
0
Order By: Relevance
“…3), the location with the highest concentration of mitochondria in the retina. The present findings are thus consistent with the previous suggestion that photoreceptor cells are the principal consumers of energy in the retina (Haugh-Scheidt et al, 1995;Demontis et al, 1997). However, until a more thorough analysis of the sources and sinks of acid flux in the retina is performed, the present findings cannot be considered conclusive.…”
Section: Relationship Of the Clock Ph And Energetic Metabolismsupporting
confidence: 94%
“…3), the location with the highest concentration of mitochondria in the retina. The present findings are thus consistent with the previous suggestion that photoreceptor cells are the principal consumers of energy in the retina (Haugh-Scheidt et al, 1995;Demontis et al, 1997). However, until a more thorough analysis of the sources and sinks of acid flux in the retina is performed, the present findings cannot be considered conclusive.…”
Section: Relationship Of the Clock Ph And Energetic Metabolismsupporting
confidence: 94%
“…The decrease in oxygen utilization with light has been found in all vertebrates that have been studied, including frog (Sickel, 1972), toad (Haugh-Scheidt et al, 1995a; Kimble et al, 1980), and rabbit (Ames et al, 1992), animals which are not otherwise considered in this review. The time course of the change in metabolism can be studied with a microelectrode placed near the inner segments while the illumination is changed, as shown in Figure 7.…”
Section: Fundamentals Of O2 Supply To the Retinamentioning
confidence: 99%
“…When the retina was in low [Na+], a light-evoked decrease in retinal PO 2 was measured in the outer retina (Haugh-Scheidt et al, 1995); however, the magnitude of the change was smaller than the light-evoked increase in PO2 in normal [Na+]. In low [Na+], the PO 2 profiles measured in light adaptation were not noticeably different from the profiles measured in dark adaptation, and the parameter values were not significantly different.…”
Section: Lowered Extracellular [Na +]mentioning
confidence: 84%
“…The QO 2 in the photoreceptor layer of the retina, in lowered [Na+], was not significantly greater in light as compared to darkness. This result was surprising given the consistent light-evoked PO2 decrease in the lowered [Na+] condition (Haugh-Scheidt et al, 1995), which indicated a QO 2 increase in the photoreceptors. The -low [Na ÷] condition, maintained for as long as necessary to measure profiles in light and dark (about 2 hr), may not maintain the retina in a stable state, judged by the slow increase in retinal PO 2 often observed in low [Na+].…”
Section: Retinal Q02mentioning
confidence: 88%